Crisis, social class, employment and education - Fernando de Lucas (Social Work and Society)
This article reviews the position of the middle classes in Spain during the economic crisis, and the impact of the crisis in the Mediterranean region. To do so, we review the transformation in Spanish social stratification during the latter years of Franco's regime and the country's adaptation to democracy within a context of European integration. The profound change in Spanish society over the last forty years has given rise to a new social structure, and has encompassed three clearly interwoven phenomena: changes in the labour market; the subsidiarity of social policy; and migratory inflows. The impacts of the economic crisis and its severe austerity measures have shaken welfare structures and, in particular, the intermediate strata. We need to focus on both the labour market and education to understand how these two aspects are coalescing into a spiral of increased intra- and inter-class polarization.